On the moroccan tsunami catalogue - Kaabouben, F. (2009)
A primary tool for regional tsunami hazard assessment is a reliable historical and instrumental catalogue of events. Morocco by its geographical situation, with two marine sides, stretching along the Atlantic coast to the west and along the Mediterranean coast to the north, is the country of Western Africa most exposed to the risk of tsunamis. Previous information on tsunami events affecting Morocco are included in the Iberian and/or the Mediterranean lists of tsunami events, as it is the case of the European GITEC Tsunami Catalogue, but there is a need to organize this information in a dataset and to assess the likelihood of claimed historical tsunamis in Morocco. Due to the fact that Moroccan sources are scarce, this compilation rely on historical documentation from neighbouring countries (Portugal and Spain) and so the compatibility between the new tsunami catalogue presented here and those that correspond to the same source areas is also discussed.